The effect of travel risk perception and destination image on visit decision in the new normal - Ridha Suci Anzani; Filda Rahmiati; Chairy Chairy; Purwanto Purwanto (Jurnal Manajemen dan Pemasaran Jasa, 2022)
The Indonesian government is serious about promoting tourism as a leading industry until COVID-19 outbreak have a huge impact on the tourism industry. Research on risk perceptions in pandemic-affected destinations is required to influence tourists in making decisions also the destination image. Thus, this study aims to examine the Travel Risk Perception on Visit Decision to an Island Tourism Destination in The New Normal. Ninety data was collected using Google Form with purposive sampling technique and analyzed using PLS-SEM. The result shows that Health Risk and Socio-psychological Risk have a direct and indirect influence through Destination Image on the Visit Decision. Financial Risk has a direct and indirect influence through Destination Image (Affective Image), whereas no indirect influence through Cognitive Image on Visit Decision. Lastly, the result of Destination Image both Cognitive and Affective Image influence Visit Decision. The study proved that perceived risk and destination image are essential for opening tourism areas in the new normal condition.